Computed Tomography and Magnetic Resonance Imaging in the Diagnosis of Cerebral Paragonimiasis in Children - Du, Jinhui; Liu, Likun; Fan, Haiqing; Yu, Yue; Luo, Yilin; Yu, Hui; Liao, Xin (Frontiers in Neurology, 2022)
Objective To investigate the computed tomography (CT) and magnetic resonance image (MRI) manifestations of cerebral paragonimiasis (CP) in children and to improve the understanding of the disease. Methods The cranial CT and MRI data of 12 children with positive intradermal tests for Paragonimus-specific antigens were retrospectively analyzed. Additionally, the lesion locations, morphology, and imaging characteristics were analyzed. Results The lesions were located in the cerebral parenchyma in 12 cases, with 10 in the supratentorial area and two in the subtentorial area, among which three cases included involvement of the meninges. The morphology of the lesions was mainly nodular and striated, with clear or indistinct borders and varying degrees of surrounding edema. The lesions showed isodense or slightly hyperdense opacities on the CT scans, heterogeneous equal or slightly decreased signal intensities on the T1-weighted images (T1WI), heterogeneous equal or slightly increased signal intensities on the T2-weighted images (T2WI), and equal or slightly increased signal intensities on the diffusion-weighted images (DWI) in MRIs. In four cases, the cyst wall showed equal T1 and short T2 signals, and in six cases, the characteristic “tunnel sign” and “worm-eaten sign” were visible. The contrast-enhanced MRI showed strip-shaped enhancement in five cases, nodular or ring-shaped enhancement in three cases, linear enhancement in two cases, and uneven enhancement in two cases. The meninges adjacent to the lesions were thickened with significant enhancement in four cases. Conclusion CP was mostly located in the cerebral parenchyma with involvement of the adjacent meninges. CT and MRI scans had certain imaging characteristics, and the MRI may particularly be of great value for the diagnosis of CP.